The use of instrumented starting blocks for sprint training - Milanese, C.; Astegno, P.; Pirlo, M.; Barbi, G.; Zancanaro, C.; Petrone, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In order to understand the starting technique, it is necessary to measure the temporal patterns of the forces generated and their correlation with the speed achieved. Up to now, such studies have been carried out in laboratory using expensive instruments. Recently, a set of dynamometric sprint blocks has been developed and used for the kinetic analysis of elite athletes in order to develop a robotic testing bench for the validation of fault start detection criteria based on reaction time [1]. The aim of this study was to design and develop a set of instrumented starting blocks able to respect all the features of those normally used in sprint start of track and equipped with a set of load cells enabling to measure the magnitude and direction of forces generated by athletes: the blocks were used as training tool during the sprint start due to their ability to provide immediate data and information to the trainer. Methods: The starting blocks were equipped with 4 axial load cells for each block. The force data are resolved into horizontal and vertical components for each foot. The system makes use of a portable personal computer to provide data acquisition, signal processing and graphical/textual display to the coach and athlete directly at the track after the start. Static and dynamic bench load tests were carried out to calibrate the force transducers. After validation, a series of sprint starts during training session with beginner, intermediate and expert athletes were recorded and compared to related force plate output. Results: Several tests were performed on each part of the apparatus to ensure the validity of the results obtained during usage. Static and dynamic load tests showed good results with low error: the difference between the maximum force applied on the block and the measured force is lower than 1%; whereas the error concerning the calculated impulse is under 4%.The blocks were used on training sessions with a group of 20 athletes, ranging from beginner to expert sprinters: force profiles were analyzed in order to recognize the patterns correlated with good starts. Discussion: The results showed that the apparatus was suitable to determine the force vector intensity and direction. Kinetic data collected with the system can be correlated with the start speed in order to classify the quality of force generation pattern. The force profiles can be displayed immediately on the screen: this feedback helped the coach in assessing the technical performance of athletes and training more effectively.